1992
DOI: 10.1002/bip.360320204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular conformation of ascidiacyclamide, a cytotoxic cyclic peptide from Ascidian: X‐ray analyses of its free form and solvate crystals

Abstract: In order to investigate the conformational variation of ascidiacyclamide, a cytotoxic cyclic peptide from marine tunicate Ascidian, single crystals were prepared from ethanol and aqueous ethanol solutions as its free form (crystal I) and H2O/0.5 C2H5OH solvate (crystal II), respectively, and were determined by the x-ray diffraction method. Crystal I showed a pseudo C2-symmetric saddle-shaped rectangular conformation. Similar conformations were also observed in crystal II, where there were two crystallographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…These parameters are summarized in Table I (nmr structure will be discussed later). In both crystal structures of [Leu] and [Ile]ASCs, the distance D and angle values, 3 which represent the stress of cyclic backbone, are similar to each other. Therefore, the replacement of Ile for Leu caused no significant change of the structure in the solid phase.…”
Section: X-ray Structurementioning
confidence: 80%
See 2 more Smart Citations
“…These parameters are summarized in Table I (nmr structure will be discussed later). In both crystal structures of [Leu] and [Ile]ASCs, the distance D and angle values, 3 which represent the stress of cyclic backbone, are similar to each other. Therefore, the replacement of Ile for Leu caused no significant change of the structure in the solid phase.…”
Section: X-ray Structurementioning
confidence: 80%
“…In the serial structure analyses, it has been shown that ascidiacyclamide is able to fold to two discrete forms at least (squared and figure 8 forms), which are characterized by the difference of the backbone twisting and the intramolecular hydrogen bond. [2][3][4][5] The similar structures have been also observed in the related tunicate peptides, patellamide A-D, and the conformational equilibrium has been postulated between the different conformers, based on nmr spectroscopic, molecular dynamics, and x-ray diffraction studies. 6 -9 It has been also considered that a "proper" pathway of the conformational change exists in the equilibrium [3][4][5] and the cytotoxicities of these tunicate peptides are brought out by their active conformations in the conformational equilibrium.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…A substantial increase in flexibility compared to the cyclic pseudo-hexa-and pseudo-heptapeptides might be expected. However, analysis of the solid state and solution structures by X-ray crystallography, 27,73,74,84,85 1 H-NMR spectroscopy, 19,33,72,85 DFT calculations 74 and molecular mechanics/ Monte Carlo/molecular dynamics-based conformational analyses 27,72 indicated that there are four conformers which we summarize here in two types of conformations: the "saddleshaped", sometimes also referred to as square, and the twisted "figure-of-eight" conformation (Fig. 4).…”
Section: Structures and Dynamicsmentioning
confidence: 85%
“…This restricts the flexibility to three distinct conformations, usually described as type 1, type 2 (saddle), and type 3 (twisted figure-ofeight). [14,37] It appears that, at least for the bis-seco(oxazoline)-type ligands (PatN, PatJ 1 , PatJ 2 , and PatL), this nomenclature is not appropriate because a) the additional flexibility must lead to further stable conformations, and b) the distinction between saddle and figure-of-eight generally depends on the orientation of the structural plot. This emerges from Figure 2, whichs shows the structures of PatJ 1 , patellamide D, and the dicopper(ii) complex of PatJ 1 .…”
Section: Resultsmentioning
confidence: 99%